Powder technology and innovative fiber design enabling a new generation of high-power single-mode-fiber laser sources - Dauliat, R.; Gaponov, D.; Jamier, R.; Schuster, K.; Grimm, S.; Valette, S.; Benoit, A.; Salin, F.; Roy, P. (ALT Proceedings, 2026)
By simultaneously providing ultra large mode effective area (ULMA) and close to diffraction limited laser beams, Yb-doped double-clad photonic crystal fibers have become key components for power scaling in fiber laser systems. Despite their advantages, such fibers suffer from some drawbacks among which tremendous fabrication complexity and arising costs, high bending losses and poor integrability. In this paper, we show how the REPUSIL technique, which is an alternate synthesis method to produce high-quality doped-silica, enables the design of a new generation of ULMA rare-earth-doped fibers. Some examples of innovative fiber designs will be shown and commented together with a first experimental demonstration of all-solid Yb-doped double-cladding fiber fabrication. The thermal effects, which play a major role at high power laser level and drastically compromise the single-mode regime, are also investigated. The very first experimental results for the fiber and laser characterization are given.